Effects of Hypericum perforatum on turning behavior in an animal model of Parkinson's disease - Débora Dalla Vecchia; Marissa Giovanna Schamne; Marcelo Machado Ferro; Ana Flávia Chaves dos Santos; Camila Lupepsa Latyki; Danilo Vieira de Lara; Juliana Ben; Eduardo Luiz Moreira; Rui Daniel Prediger; Edmar Miyoshi (Universidade de São Paulo, 2015)
Parkinson's disease (PD) is an age-related neurodegenerative disorder characterized by the slow and progressive death of dopaminergic neurons in the (substantia nigra pars compact). Hypericum perforatum (H. perforatum) is a plant widely used as an antidepressant, that also presents antioxidant and anti-inflammatory properties. We evaluated the effects of H. perforatum on the turning behavior of rats submitted to a unilateral administration of 6-hydroxydopamine (6-OHDA) into the medial forebrain bundle as an animal model of PD. The animals were treated with H. perforatum (100, 200, or 400 mg/kg, v.o.) for 35 consecutive days (from the 28th day before surgery to the 7th day after). The turning behavior was evaluated at 7, 14 and 21 days after the surgery, and the turnings were counted as contralateral or ipsilateral to the lesion side. All tested doses significantly reduced the number of contralateral turns in all days of evaluation, suggesting a neuroprotective effect. However, they were not able to prevent the 6-OHDA-induced decrease of tyrosine hydroxylase expression in the lesioned striatum. We propose that H. perforatum may counteract the overexpression of dopamine receptors on the lesioned striatum as a possible mechanism for this effect. The present findings provide new evidence that H. perforatum may represent a promising therapeutic tool for PD.